Do oxidized fatty acids activate coagulation factor VII during post-prandial lipemia in women? - Wilson, Robert; Lyall, Karin; Millar, Margaret E.; Smyth, Louise; Pearson, Claire; Riemersma, Rudolph A. (Thrombosis and Haemostasis, 2003)
Factor VII is activated to VIIa within hours after dietary fat, irrespective of its fatty acid composition. Edible oils contain oxidized material (hydroxy fatty acids, HOFA). Twenty-five fasting women, aged 38 (10) years, consumed 30 g walnut oil containing 26 (6) mg HOFA. Blood was collected 2-hourly to measure plasma triglycerides and plasma lipid HOFA by gas chromatography/mass spectrometry. VII and sTF-dependent VIIa were quantified at 0, 6 and 24 h. Increased plasma triglycerides and HOFA (areas under the-curve 0-8 h, AUC) were related r = 0.83, p <0.001. VIIa increased from 2.6 (1.4) to 4.2 (1.9) ng/mL at 6 h (p <0.001). Plasma VII remained constant. VIIa (6 h) was related to plasma triglycerides- and HOFA-AUC: r = 0.38 and 0.53, respectively (both p <0.05). Plasma VIIa was also related to body weight, fasting triglycerides, HOFA and VII. Only HOFA-AUC and body weight related to VIIa (6 h) in stepwise regression analysis (p = 0.007 and 0.038, respectively). Oxidized, not normal, fat activates VII and could increase coronary risk in humans.
Keywords: Lipid peroxidation; factor VIIa; post-prandial lipemia; diet